1986
DOI: 10.1177/0093854886013003005
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Stressors among Federal Correctional Officers Working in Different Security Levels

Abstract: This study investigated distress and self-esteem levels of 147 federal correctional officers working in that system's six different security level institutions. The General Severity Index (GSI), a scale of the Brief Symptom Inventory (BSI), was used to measure distress; the Rosenberg Self-Esteem Scale (SES) operationalized the other dependent variable. In addition, 13 variables were used as part of a multiple regression analysis to determine a prediction equation for the two outcomes studied. Lack of participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 6 publications
1
35
1
1
Order By: Relevance
“…Studies that utilized physiological measures of stress (i.e., Lasky, Gordon, & Srebalus, 1986;Pollack & Sigler, 1998, etc. ) were excluded to maintain consistency of outcome measures as well as to control for the lack of systematic study present in the field of correctional officer stress (Huckabee, 1992).…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…Studies that utilized physiological measures of stress (i.e., Lasky, Gordon, & Srebalus, 1986;Pollack & Sigler, 1998, etc. ) were excluded to maintain consistency of outcome measures as well as to control for the lack of systematic study present in the field of correctional officer stress (Huckabee, 1992).…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…Numerous studies in the United States found various explanations for correctional officer stress (Blau et al, 1986;Cheek & Miller, 1983;Cullen et al, 1985Cullen et al, , 1990Finn, 2000;Grossi & Berg, 1991;Hepburn & Albonetti, 1980;Jacobs, 1978;Lasky et al, 1986;Maghan & McLeish-Blackwell, 1991;Mitchell et al, 2000;Poole & Regoli, 1980;Triplett et al, 1996). Among the explanations cited, role conflict and role ambiguity were found by many researchers to be among the main sources of stress (Brodsky, 1982;Cheek & Miller, 1983;Cullen et al, 1990;Finn, 2000;Hepburn & Albonetti, 1980;Lasky et al, 1986;Mitchell et al, 2000;Poole & Regoli, 1980).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In as much as their roles are important in penal institutions, however, there are also pressing problems inherent in their roles (Finn, 2000;Poole & Regoli, 1980;Shamir & Drory, 1982;Triplett, Mullings, & Scarborough, 1996;Walters, 1996;Whitehead & Lindquist, 1989). In particular, researchers have long documented the prevalence of work-related stress among corrections officers, the problems associated with this stress, and the variety of reasons for the stress (Blau, Light, & Chamlin, 1986;Cheek & Miller, 1983;Cullen, Link, Cullen, & Wolfe, 1990;Cullen, Link, Wolfe, & Frank, 1985;Finn, 2000;Grossi & Berg, 1991;Hepburn & Albonetti, 1980;Jacobs, 1978;Lasky, Gordon, & Srebalus, 1986;Maghan & McLeishBlackwell, 1991;Mitchell, Mackenzie, Styve, & Gover, 2000;Poole & Regoli, 1980;Triplett et al, 1996). Many studies, for example, found that corrections officers experienced excessive levels of stress related to such reasons as prison overcrowding, the life-threatening aspects of correctional work, rotating shifts, role conflict and ambiguity, conflict with administrators, and even negative public image (Cheek & Miller, 1983;Cullen et al, 1990;Finn, 2000;Jacobs, 1978;Maghan & McLeish-Blackwell, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The BSI has been widely used in studies investigating psychological distress in prison settings (e.g. Gibbs, 1987;Lasky et al, 1986). …”
Section: Instrumentsmentioning
confidence: 99%